PENGARUH MODEL ATTENTION RELEVANCE CONFIDENCE SATISFACTION TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA MATERI SISTEM INDERA - lulu Kholbi; R. Ading Pramadi; Asrianty Mas'ud (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2020)
Student activeness and interaction between teacher and students during the learning process is still lacking so that it can affect student learning outcomes. The objectives of this study are: (1) to find out how the learning process of the sensory system uses the ARCS model, (2) find out how to improve student learning outcomes in the material sensory system with and without the ARCS model. The method used is a quasi-experimental study with a form of nonequivalent control group design. The procedure is done by giving a pretest, implementing learning, giving posttets, and drawing conclusions from the results of research. Analysis of research data includes normality test, homogeneity test, hypothesis test and N-Gain test. Data were obtained from 15 pretest and posttest multiple choice questions. Based on the analysis results obtained tcount = 2.26 and table = 2.00 at a significance level of 5%. It can be concluded that the ARCS Model has a positive effect on improving student learning outcomes in the material sensory system. Keywords: ARCS model, improvement of learning outcomes, sensory system. Abstrak. Keaktifan siswa dan interaksi antara guru dan siswa selama pembelajaran berlangsung masih kurang sehingga dapat berpengaruh kepada hasil belajar siswa. Tujuan dari penelitian ini adalah: (1) mengetahui bagaimana keterlaksanaan proses pembelajaran sistem indera dengan menggunakan model ARCS, (2) mengetahui bagaimana peningkatan hasil belajar siswa pada materi sistem indera dengan dan tanpa model ARCS. Metode yang digunakan adalah penelitian quasi eksperimen dengan bentuk nonequivalent control group design. Prosedur yang dilakukan dengan pemberian pretest, pelaksanaan pembelajaran, pemberian posttets, dan penarikan kesimpulan hasil penelitian. Analisis data penelitian meliputi uji normalitas, uji homogenitas, uji hipotesis serta uji N-Gain. Data diperoleh dari 15 soal pilihan ganda pretest dan posttest. Berdasarkan hasil analisis diperoleh nilai thitung = 2,26 dan ttabel = 2,00 pada taraf siginifikansi 5%. Dapat disimpulkan bahwa Model ARCS berpengaruh positif tehadap peningkatan hasil belajar siswa pada materi sistem indera.